Flora de manutenção para apis mellifera no município de Paramoti-Ceará-Brasil - Reis, Ígor Torres (2009)
The experiment was conducted at the Rosa dos Ventos farm, on the county of Paramoti - Ceará - Brazil. from july to december 2008, with the aim of indenitfying botanic species of the caatinga wich are important as feeding sources for the maintenance of Apis mellifera colonies in the county of Paramoti - CE. Have been choosen, randomly, fifteen colonies of africanized bees (Apis mellifera) from a pool of tirty colonies, keeping among them uniformity relating to the population. Among these fifteen colonies, five were randomly choosen to acquire polen samples, five to acquire honey samples, keeping the remaining five in backup condition. The polen samples, which were weekly collected, were submitted to palinoligic analisys. A botanic survey was conducted in the area, taking into account all of the strata: arboreum, arbustive and aerbaceum. The results showed that 71 botanic species flourishing during the experiment, but only 28 species participated in the polen and nectar diet of the bees. Main vegetal species which contributed to the polen supply during the estiagem season were: jurema-preta (Mimosa tenuiflora (Willd.) Poir), angico (Anadenanthera Colubrina (Vell.)), mutamba (Guazuma ulmifolia), vassourinha de botão (Spermacoce verticillata), malva branca (Waltheria indica), erva de touro (Tridax procumbens L), algaroba (Prosopis juliflora (Sw.) Dc) e melosa (Angilonia biflora Benth). During the months of july, august and september the species wich had the most participation on the diet of the bees was jurema-preta with 44.42%; 59.94%; 30.38% respectively, during october it was angico 29.97%, jurema-preta with 20.36% and melosa with 20.36%, during november there was predominance of jurema-preta with 38.08% and angico with 29.81%, in december the species wich predominated was mutamba with 34.86%. The other remaining species had their participation, but under excess 12.72% of contribution on the diet of the bees. The jurema-preta had a significant participation from july to december. So been very important as proteic source in the feeding of the bees during the estiagem season. The melissopalinologic analisys showed the following polinic types: jurema preta (Mimosa tenuiflora (Willd.) Poir.), algaroba (Prosopis juliflora (Sw)), jitirana roxa (Ipomoea fimbriosepala Choisy), vassourinha de botão (Spermacoce verticillata), quebra-panela (Alternamthera brasiliana), melosa (Angilonia biflora Benth) e cajueiro (Anacardium occidentale). It is concluded that the caatinga has species which provide polen and/or nectar been arboreum the main provider strata with the following species: jurema-preta (Mimosa tenuiflora (Willd.) Poir), angico (Anadenathera colubrina), mutamba (Guazuma ulmifolia) e algaroba (Prosopis juliflora), cajueiro (Anacardium occidentale). The jurema-preta was the species which most contributed with polen for the colony, been recommendable its conservation and expansion of the number of plants in the area of bee development.